The spatial distribution pattern of Connexin26 expression in supporting cells and its role in outer hair cell survival. Issue 12 (December 2018) - Chen, Sen; Xu, Kai; Xie, Le; Cao, Hai-Yan; Wu, Xia; Du, An-Na; He, Zu-Hong; Lin, Xi; Sun, Yu; Kong, Wei-Jia
Abstract Mutations in theGJB2 gene (which encodes Connexin26 (Cx26)) account for about a quarter of all cases of non-syndromic deafness. Previous studies have indicated that knockout (KO) ofGjb2 gene during early postnatal days can cause outer hair cell (OHC) loss in mouse models. However, the postnatal spatial distribution pattern of Cx26 in different types of supporting cells (SCs) and the role of such distributions for the survival of OHCs is still obscure. In this study, the spatial distribution patterns of Cx26 in SCs were observed, and based on these observations different spatial Cx26-null mouse models were established in order to determine the effect of changes in the spatial distribution of Cx26 in SCs on the survival of OHCs. At postnatal day (P)3, unlike the synchronous expression of Cx26 along both longitudinal and radial boundaries of most types of SCs, Cx26 expression was primarily observed along the longitudinal boundaries of rows of Deiter's cells (DCs). From P5 to P7, radial expression of Cx26 was gradually observed between adjacent rows of DCs. WhenGjb2 gene was knocked out at random in different types of SCs, about 40% of the total DCs lost Cx26 expression and these Cx26-null DCs were distributed randomly in all three rows of DCs. The mice in this randomly Cx26-null group showed normal hearing and no significant OHC loss. When using a longitudinal KO pattern to induce knockout ofGjb2 gene specifically in the third row of DCs, about 33% of the total DCs lost Cx26 expression in this specific longitudinally Cx26-null group. The mice in this group showed late-onset hearing loss and significant OHC loss, however, the morphology of corresponding DCs was slightly altered. In both experimental groups, no substantial DC loss was observed. These results indicate that longitudinal Cx26-based channels are predominant in DCs during P3–P5. The Cx26 expression along rows of DCs might play a key role in the survival of OHCs, but this longitudinal KO pattern in DCs has a limited effect on DC survival or on its postnatal development.